55th AIAA Aerospace Sciences Meeting 2017
DOI: 10.2514/6.2017-1853
|View full text |Cite
|
Sign up to set email alerts
|

Relating a Jet-Surface Interaction Experiment to a Commercial Supersonic Transport Aircraft Using Numerical Simulations

Abstract: Reynolds-Averaged Navier-Stokes (RANS) simulations were performed for a commercial supersonic transport aircraft concept and experimental hardware models designed to represent the installed propulsion system of the conceptual aircraft in an upcoming test campaign. The purpose of the experiment is to determine the effects of jet-surface interactions from supersonic aircraft on airport community noise. RANS simulations of the commercial supersonic transport aircraft concept were performed to relate the represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The volume grid also included node clustering around the plume regions, with node spacing of 2 inches. An initial plume grid study showed lower than expected values of turbulent kinetic energy (tke) within the plume regions based on earlier simulations of a similar isolated nozzle configuration 7 . The spacing between nodes within the plume regions was subsequently halved, with results shown in Fig 6.…”
Section: A Geometry and Grid Representationmentioning
confidence: 80%
See 1 more Smart Citation
“…The volume grid also included node clustering around the plume regions, with node spacing of 2 inches. An initial plume grid study showed lower than expected values of turbulent kinetic energy (tke) within the plume regions based on earlier simulations of a similar isolated nozzle configuration 7 . The spacing between nodes within the plume regions was subsequently halved, with results shown in Fig 6.…”
Section: A Geometry and Grid Representationmentioning
confidence: 80%
“…The Lockheed Martin LM1044-3b, a conceptual N+2 commercial supersonic transport aircraft 4 shown in Fig. 1, has been used in prior studies to better understand jet-surface interactions and to explore jet noise reduction techniques [5][6][7][8] . One such technique was to move the engines from underneath the wings to above the wings, which would allow for potential jet noise shielding relative to ground observers.…”
Section: Introductionmentioning
confidence: 99%